2013
DOI: 10.1002/aur.1264
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of NMDA Receptors in Parvalbumin Interneurons Recreates Autism‐Like Phenotypes

Abstract: Autism is a disabling neurodevelopmental disorder characterized by social deficits, language impairment, and repetitive behaviors with few effective treatments. New evidence suggests that autism has reliable electrophysiological endophenotypes and that these measures may be caused by n-methyl-d-aspartic acid receptor (NMDAR) disruption on parvalbumin (PV)-containing interneurons. These findings could be used to create new translational biomarkers. Recent developments have allowed for cell-type selective knocko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
66
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 34 publications
4
66
1
Order By: Relevance
“…Further, our pharmacological data support dysregulation of GABAergic and glutamatergic signaling in mutants. Altered NMDA signaling has been shown to cause GABAergic deficits, particularly in parvalbumin-positive (PV+) interneurons, and has been proposed as a mechanism underlying neuropsychiatric disorders (Keilhoff et al, 2004; Saunders et al, 2013). Moreover, mouse Cntnap2 knockouts display GABAergic deficits, most prominently in PV+ interneurons (Penagarikano et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Further, our pharmacological data support dysregulation of GABAergic and glutamatergic signaling in mutants. Altered NMDA signaling has been shown to cause GABAergic deficits, particularly in parvalbumin-positive (PV+) interneurons, and has been proposed as a mechanism underlying neuropsychiatric disorders (Keilhoff et al, 2004; Saunders et al, 2013). Moreover, mouse Cntnap2 knockouts display GABAergic deficits, most prominently in PV+ interneurons (Penagarikano et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In ASD, a growing body of research has shown GABA receptors to be downregulated in ASD (Fatemi et al 2009), and ASD participants have shown decreased gamma-band oscillatory activity compared to controls (Wilson et al 2007; Rojas et al 2008; Orekhova et al 2007). Interneurons defined by the fast-spiking phenotype and expression of the calcium-binding protein parvalbumin have been implicated in gamma oscillations (e.g., (Tamas et al 2000; Whittington et al 1995), and in vivo mouse studies show that inhibiting parvalbumin interneurons suppresses gamma oscillations whereas driving these interneurons is sufficient to generate emergent gamma oscillations (Saunders et al 2013; Sohal et al 2009). With regard to the pre-stimulus group differences observed in the present study, it is worth noting that optogenetic inhibition of fast-spiking interneurons reduced stimulus-evoked gamma synchrony and also caused an increase in baseline LFP power in the absence of a stimulus (2013).…”
Section: Discussionmentioning
confidence: 99%
“…Autism has been reliably associated with electrophysiological endophenotypes that may be caused by NMDA receptor disruption on parvalbumin (PV)-containing interneurons [133]. In human, M1 (N1 event-related potential as measured by magneto-encephalography) latency is shifted by approximately 10% in ASD patients [134].…”
Section: Nmda Receptor Dysfunction Is Involved In Various Disordersmentioning
confidence: 99%
“…The N1 event-related potential is a negative peak approximately 100 ms after sensory stimulation that is linked to early attention [135]. In PV containing cell-type selective GluN1 KO mice, delayed N1 event-related potential latency, reduced sociability, and impairment of mating-related USVs are observed [133]. In mice, social behavior is known to be expressed as social investigation, intermale aggression, sexual behavior, and parental behavior.…”
Section: Nmda Receptor Dysfunction Is Involved In Various Disordersmentioning
confidence: 99%
See 1 more Smart Citation